Amer1/WTX couples Wnt-induced formation of PtdIns(4,5)P2 to LRP6 phosphorylation - Tanneberger, Kristina; Pfister, Astrid S; Brauburger, Katharina; Schneikert, Jean; Hadjihannas, Michel V; Kriz, Vitezslav; Schulte, Gunnar; Bryja, Vitezslav; Behrens, Jürgen (The EMBO journal, 2011)
Phosphorylation of the Wnt receptor low‐density lipoprotein receptor‐related protein 6 (LRP6) by glycogen synthase kinase 3β (GSK3β) and casein kinase 1γ (CK1γ) is a key step in Wnt/β‐catenin signalling, which requires Wnt‐induced formation of phosphatidylinositol 4,5‐bisphosphate (PtdIns(4,5)P 2 ). Here, we show that adenomatous polyposis coli membrane recruitment 1 (Amer1) (also called WTX), a membrane associated PtdIns(4,5)P 2 ‐binding protein, is essential for the activation of Wnt signalling at the LRP6 receptor level. Knockdown of Amer1 reduces Wnt‐induced LRP6 phosphorylation, Axin translocation to the plasma membrane and formation of LRP6 signalosomes. Overexpression of Amer1 promotes LRP6 phosphorylation, which requires interaction of Amer1 with PtdIns(4,5)P 2 . Amer1 translocates to the plasma membrane in a PtdIns(4,5)P 2 ‐dependent manner after Wnt treatment and is required for LRP6 phosphorylation stimulated by application of PtdIns(4,5)P 2 . Amer1 binds CK1γ, recruits Axin and GSK3β to the plasma membrane and promotes complex formation between Axin and LRP6. Fusion of Amer1 to the cytoplasmic domain of LRP6 induces LRP6 phosphorylation and stimulates robust Wnt/β‐catenin signalling. We propose a mechanism for Wnt receptor activation by which generation of PtdIns(4,5)P 2 leads to recruitment of Amer1 to the plasma membrane, which acts as a scaffold protein to stimulate phosphorylation of LRP6. Amer1/WTX has previously been shown to promote β‐catenin degradation. Here, the authors uncover an unexpected role of Amer1/WTX as a positive regulator of Wnt signalling. Amer/WTX acts as a scaffold protein that is recruited to the plasma membrane in response to Wnt stimulation and is needed for the phosphorylation and activation of the LRP6 receptor.